Ultrathin palladium-tin nanonet catalyst as well as preparation method and application thereof
Through the application of ultra-thin palladium-tin nanomesh catalyst, the problems of slow kinetics of ethanol oxidation reaction and low C1 path selectivity in direct ethanol fuel cells are solved, and high activity and high selectivity ethanol oxidation is achieved, which significantly improves the energy conversion efficiency.
Patent Information
- Application Number
- CN202510206091.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The practical application of direct ethanol fuel cells is subject to the problem of slow kinetics of the anode ethanol oxidation reaction and incomplete reaction, especially the low selectivity of the C1 path, which limits the energy conversion efficiency.
Ultrathin palladium-tin nanomesh catalyst is used, which is rapidly synthesized by a simple one-step method. Ultrathin two-dimensional structure and mesh structure with atomic thickness significantly increases the proportion of edge low-coordinated atoms and is applied to ethanol oxidation reaction.
The electrocatalytic ethanol oxidation has been achieved with high activity and high C1 selectivity, and the electrochemical activity area and mass activity of the catalyst is significantly higher than that of the existing technology, and has good market prospects.
Smart Images

Figure CN119681279A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical catalysts, and in particular relates to an ultra-thin palladium-tin nano-mesh catalyst and a preparation method and application thereof. Background Art
[0002] With the continuous intensification of the energy crisis and the increasing severity of environmental pollution, the global energy utilization pattern is undergoing major changes. Exploring new ways of clean, efficient and sustainable energy utilization has become a research hotspot in the world today. Hydrogen-oxygen fuel cells using hydrogen as fuel have become the fastest-growing fuel cells to date. However, there are currently major bottlenecks and safety hazards in the production, storage and transportation of hydrogen, which restrict the development and practical application of hydrogen-oxygen fuel cells. Direct alcohol fuel cells are a new type of fuel cell using liquid alcohols as fuel. Due to their low storage risk, easy replenishment and high energy density, they are considered to be a very promising energy device. In terms of the selection of anode fuel for direct alcohol fuel cells, compared with the simplest structure of methanol, ethanol as a fuel has lower toxicity, lower membrane permeability, higher energy density and biorenewability.
[0003] However, the practical application of direct ethanol fuel cells is severely hampered by the sluggish kinetics and incomplete reaction of ethanol oxidation at the anode. It is generally believed that the ethanol oxidation reaction follows two parallel and competing pathways. 2 The complete ethanol oxidation pathway (C1 pathway) involves 12 electron transfers and CC bond cleavage, while the C2 pathway from ethanol to acetaldehyde / acetic acid involves 2 / 4 electron transfers without breaking the CC bond. Obviously, improving the selectivity of the C1 pathway is of great significance for improving the energy conversion efficiency of direct ethanol fuel cells. However, to date, platinum (Pt) and palladium (Pd) are considered to be the most advanced single metal catalysts for ethanol oxidation reactions. However, the selectivity of the C1 pathway on pure Pt and Pd catalysts is still very low (<7.5%).
[0004] With the rapid development of anion exchange membranes and cathode oxygen reduction reaction electrocatalysts, alkaline direct ethanol fuel cells are receiving increasing attention. The performance of alkaline direct ethanol fuel cells has been significantly improved because the kinetics of the anodic ethanol oxidation reaction and the cathode oxygen reduction reaction in alkaline electrolytes are more favorable than those in acidic electrolytes. In alkaline electrolytes, the ethanol oxidation activity of Pd is significantly higher than that of Pt and reaches the highest among all known single metal catalysts. Therefore, the development of Pd-based ethanol oxidation electrocatalysts is believed to help promote the development and application of alkaline direct ethanol fuel cells. A common catalyst optimization strategy is to alloy Pd with other oxophilic metals such as tin, iron, nickel and zinc. The enhanced catalytic performance is mainly attributed to the bifunctional mechanism. The easy adsorption of O and OH on the oxophilic sites of the catalyst can promote the removal of toxic intermediates, thereby improving the activity and stability of the ethanol oxidation reaction. However, it is still difficult to solve the problem of low selectivity of the C1 pathway through this alloying strategy.
[0005] Recently, low-coordination site engineering has been considered as a promising catalyst design strategy to effectively improve the performance of electrocatalysts. Ultrathin two-dimensional nanosheets with atomic thickness are a new type of catalyst material to achieve high density of low-coordination atoms. Due to their excellent properties such as high atom utilization, excellent electron mobility and abundant low-coordination edge sites, ultrathin two-dimensional noble metal nanosheets show broad prospects in electrocatalytic applications. However, the low-coordination atoms in ultrathin two-dimensional nanosheet materials are mainly located at the edge of the nanosheets, while a large number of atoms on the inner surface maintain a relatively high coordination number, resulting in a relatively low proportion of low-coordination sites, and the C1 path selectivity and catalytic activity of the catalyst are still not high. Summary of the invention
[0006] In order to solve the above problems, the present invention provides an ultrathin palladium tin nanomesh catalyst and its preparation method and application. The present invention uses a simple one-step method to quickly synthesize an ultrathin two-dimensional palladium tin nanomesh catalyst with atomic-level thickness. The mesh structure makes it have a significantly higher proportion of edge low-coordinated atoms compared with the nanosheet structure, and the material is applied to the ethanol oxidation reaction, achieving high activity and high C1 selectivity of electrocatalytic ethanol oxidation.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions: The present invention provides a method for preparing an ultrathin palladium-tin nano-mesh catalyst, which comprises the following steps: (1) Mix N,N-dimethylformamide and etchant evenly; (2) dissolving the precursor, sacrificial pore-forming material, and tungsten hexacarbonyl in the mixed solution of step (1), heating the solution at high temperature, cooling the solution to room temperature, and washing the solution by centrifugation to obtain an ultrathin palladium-tin nanonet catalyst; The precursors are palladium metal salt and tin metal salt; the sacrificial pore-forming substance is at least one of iron metal salt and zinc metal salt.
[0008] Furthermore, the palladium metal salt is sodium chloropalladate, and the tin metal salt is tin chloride.
[0009] Furthermore, the iron metal salt is ferric chloride, and the zinc metal salt is zinc chloride.
[0010] Furthermore, the mass ratio of the sodium chloropalladate to tin chloride is 1-1.5:1.
[0011] Furthermore, the mass ratio of the precursor to the sacrificial pore-forming substance is 2-3:1.
[0012] Furthermore, the mass ratio of the precursor to tungsten hexacarbonyl is 1:1.5-2.
[0013] Furthermore, the etchant is acetic acid; and the volume ratio of the N,N-dimethylformamide to the etchant is 4-5:1.
[0014] Furthermore, the target temperature of the high temperature heating is 140°C-180°C, and the temperature is reached within 15 minutes, and the heating time is 1-1.5 hours.
[0015] Preferably, the target temperature of the high temperature heating is 160°C.
[0016] The present invention also provides an ultra-thin palladium tin nano-mesh catalyst, which is prepared by the preparation method and has an electrochemical active area of 55-60 m 2 / g Pd , with an ultra-thin structure with a thickness of less than 1 nm.
[0017] Furthermore, the network structure of the ultra-thin palladium-tin nanomesh catalyst provides it with a large number of edge low-coordination atomic sites.
[0018] The present invention also provides the use of the ultra-thin palladium-tin nano-mesh catalyst in direct ethanol fuel cells or electrocatalytic ethanol oxidation.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention utilizes a simple one-step method to rapidly realize the synthesis of an ultra-thin two-dimensional palladium-tin nanomesh catalyst with atomic-level thickness, and does not require the addition of an additional surfactant. The mesh structure is manufactured by etching a sacrificial metal and the sheet-like macrostructure is maintained; the ultra-thin characteristics and mesh structure enable it to have a significantly higher proportion of edge low-coordinated atoms and a higher electrochemically active area compared to the nanosheet structure. The present invention also applies the material to the ethanol oxidation reaction, achieving high activity and high C1 selectivity for electrocatalytic ethanol oxidation. In addition, the present invention does not involve secondary heating or the addition of a surfactant, thereby making the ultra-thin two-dimensional palladium-tin nanomesh catalyst easy to clean and simple to synthesize, and the mass activity of the synthesized catalyst is 10.8 A / mg Pd The specific surface area activity is 22.1 mA / cm 2 , the electrochemical active area is 57.0m 2 / g Pd , which are significantly higher than the existing technology, so it has a good market prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is an electron microscope image of the PdSn nanonet of Example 1; wherein a is a scanning electron microscope (SEM) image of the PdSn nanonet, b is a transmission electron microscope (TEM) image of the PdSn nanonet, and c is Figure 1 An enlarged view of a portion of the area in b.
[0021] Figure 2 The atomic force microscope (AFM) image and thickness distribution diagram of the PdSn nanomesh in Example 1 are shown.
[0022] Figure 3 This is the TEM image of the PdSn nanomesh corresponding to Example 2.
[0023] Figure 4 This is the TEM image of the PdSn nanomesh corresponding to Example 3.
[0024] Figure 5 This is the TEM image of the PdSn nanomesh corresponding to Example 4.
[0025] Figure 6 These are the SEM and TEM images of the Pd nanosheets corresponding to Comparative Example 1; wherein a is the SEM image of the Pd nanosheets, and b and c are the TEM images of the Pd nanosheets.
[0026] Figure 7 These are the SEM and TEM images of the PdSn nanosheets corresponding to Comparative Example 2; wherein a is the SEM image of the PdSn nanosheets, and b and c are the TEM images of the PdSn nanosheets.
[0027] Figure 8X-ray diffraction (XRD) patterns of Pd nanosheets loaded on carbon powder (Pd nanosheets / C) corresponding to comparative example 1, PdSn nanosheets loaded on carbon powder (PdSn nanosheets / C) corresponding to comparative example 2, and PdSn nanomesh loaded on carbon powder (PdSn nanomesh / C) corresponding to example 2.
[0028] Fig. 9 Comparison of specific surface area activity and mass activity of commercial Pd / C, Pd nanosheets / C, PdSn nanosheets / C and PdSn nanomesh / C for electrocatalytic ethanol oxidation; a is the specific surface area activity curve, b is the mass activity curve, and c is a summary comparison of the highest specific surface area activity and the highest mass activity.
[0029] Fig.10 Comparison of the Faradaic efficiency of the C1 path of commercial Pd / C, Pd nanosheets / C, PdSn nanosheets / C and PdSn nanomesh / C for electrocatalytic ethanol oxidation. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail with reference to the following specific examples.
[0031] In the following examples, unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used can be purchased from biological or chemical reagent companies.
[0032] Example 1 11.3 mg of sodium chloropalladate hydrate, 8.5 mg of tin chloride hydrate, 6.8 mg of ferric chloride hydrate and 31 mg of hexacarbonyl tungsten were dissolved in a round-bottom flask filled with a mixed solution of 8 mL of N,N-dimethylformamide and 2 mL of acetic acid, the flask was sealed, and then heated to 160 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was naturally cooled to room temperature, the product PdSn nanonet was collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0033] Example 2 11.3 mg of sodium chloropalladate hydrate, 8.5 mg of tin chloride hydrate, 8.0 mg of zinc chloride hydrate and 31 mg of hexacarbonyl tungsten were dissolved in a round-bottom flask filled with a mixed solution of 8 mL of N,N-dimethylformamide and 2 mL of acetic acid, the flask was sealed, and then heated to 160 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was naturally cooled to room temperature, the product PdSn nanonet was collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0034] Example 3 11.3 mg sodium chloropalladate hydrate, 8.5 mg tin chloride hydrate, 6.8 mg ferric chloride hydrate and 31 mg tungsten hexacarbonyl were dissolved in a round-bottom flask filled with a mixed solution of 8 mL N,N-dimethylformamide and 2 mL acetic acid, the flask was sealed, and then heated to 140 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was cooled to room temperature naturally, the product PdSn nanonet was collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0035] Example 4 11.3 mg sodium chloropalladate hydrate, 8.5 mg tin chloride hydrate, 6.8 mg ferric chloride hydrate and 31 mg tungsten hexacarbonyl were dissolved in a round-bottom flask filled with a mixed solution of 8 mL N,N-dimethylformamide and 2 mL acetic acid, the flask was sealed, and then heated to 180 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was naturally cooled to room temperature, the product PdSn nanonet was collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0036] Comparative Example 1 11.3 mg of sodium chloropalladate hydrate and 31 mg of hexacarbonyl tungsten were dissolved in a round-bottom flask filled with a mixed solution of 8 mL of N,N-dimethylformamide and 2 mL of acetic acid, the flask was sealed, and then heated to 160 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was naturally cooled to room temperature, the product Pd nanosheets were collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0037] Comparative Example 2 11.3 mg of sodium chloropalladate hydrate, 8.5 mg of tin chloride hydrate and 31 mg of hexacarbonyl tungsten were dissolved in a round-bottom flask filled with a mixed solution of 8 mL of N,N-dimethylformamide and 2 mL of acetic acid, the flask was sealed, and then heated to 160 ° C within 15 minutes and kept under magnetic stirring for 1 hour. After the mixture was naturally cooled to room temperature, the product PdSn nanosheets were collected by washing three times with ethanol by centrifugation at 6000 rpm for 5 minutes.
[0038] Example 5 1. Characterization methods (1) Morphology analysis The morphology of the nanomaterials synthesized in the examples and comparative examples was characterized using a scanning electron microscope (SEM) and a transmission electron microscope (TEM), and the thickness of the nanomaterials was characterized using an atomic force microscope (AFM).
[0039] (2) Loading of nanomaterials To facilitate subsequent physicochemical tests, the nanomaterials prepared in the examples and comparative examples were loaded on Ketjen carbon for further characterization. In short, the collected nanomaterials and 13 mg Ketjen carbon were mixed in 10 mL of ethanol and ultrasonicated for 30 minutes. The mixture was stirred overnight to ensure that the material was evenly deposited on the carbon. The product was collected by centrifugation at 8000 rpm for 5 minutes and dried overnight at 60 ° C under vacuum to obtain the corresponding loaded nanomaterial, i.e., carbon-supported catalyst.
[0040] (3) Elemental composition and crystal structure analysis The obtained carbon-supported catalyst was digested with aqua regia, and the proportion of the metal components of the catalyst was analyzed by inductively coupled plasma mass spectrometry (ICP-MS). The crystal structure of the obtained carbon-supported catalyst material was characterized by X-ray diffractometer (XRD).
[0041] (4) Electrochemical testing 4 mg of carbon-supported catalyst material was added with 1 mL of ultrapure water, 1 mL of isopropanol and 30 μL of Nafion solution. After sufficient ultrasonic dispersion, 5 μL was drop-coated on a rotating disk glassy carbon electrode for electrochemical testing. The electrochemical active area of the catalyst was tested by CO stripping experiment. First, CO was passed into the electrolyte for at least 10 minutes to ensure that the CO molecules were completely adsorbed on the catalyst; then, the electrode was immersed in fresh nitrogen-saturated electrode solution. CO stripping cyclic voltammograms were recorded in the potential range of 0 to 1.2 V (vs. RHE) at a scan rate of 20 mV / s. The electrolyte solution for the electrocatalytic ethanol oxidation test was 1 M NaOH + 1 M ethanol, the counter electrode was a graphite rod, the reference electrode was Hg / HgO, and the scan rate was 50 mV / s.
[0042] The H cell test was performed on the products of ethanol oxidation reaction, and the compartments of the working electrode and the reference electrode were separated from another compartment of the counter electrode by an anion exchange membrane. 1 mg of catalyst was coated on carbon paper as the working electrode, and Hg / HgO electrode and graphite rod were used as reference electrode and counter electrode. The working electrode was maintained at a constant potential of 0.6 V, 0.7 V, and 0.8 V (vs. reversible hydrogen electrode) in 1 M NaOH and 1 M ethanol. After 3 h of electrolysis, the solution from the anode compartment was collected for further product analysis.
[0043] 2. Characterization conclusion SEM and TEM images ( Figure 1 ) shows that the nanomaterial synthesized in Example 1 presents a flower-like assembly structure self-assembled from ultrathin nanosheets. The enlarged TEM image ( Figure 1c) shows that there are abundant holes in the nanosheets, and the nanosheets maintain an interconnected network structure. The structural characteristics of the nanonet make the material have a large number of edge low-coordinated atoms. AFM image ( Figure 2 ) shows that the thickness of the material is less than 1 nm, indicating that it forms an ultra-thin two-dimensional structure with atomic thickness. The final Pd / Sn / Fe atomic ratio in the product obtained in Example 1 is 73.8: 25.6: 0.6 as measured by inductively coupled plasma mass spectrometry (ICP-MS), which indicates that the content of Fe element in this material is negligible. Combined with the characterization of the subsequent comparative examples, it can be seen that active metal elements such as Fe element that are easily etched by acetic acid are the key to forming a nano-mesh structure.
[0044] Example 2 is to replace the iron precursor in Example 1 with a zinc precursor. TEM images ( Figure 3 ) characterization shows that an ultra-thin nano-mesh structure similar to that of Example 1 is also formed. ICP-MS also confirms that the content of zinc in the product is negligible, and zinc can also be etched as an active metal.
[0045] Examples 3 and 4 are obtained by changing the heating temperature of Example 1 to 140°C and 180°C, respectively. Figure 4 and Figure 5 ) characterization shows that nano-mesh structures can be synthesized at 140-180 degrees, but some mesh structures at 140°C are not connected to other mesh structures, which may be due to the slow reaction rate caused by the low temperature; the nano-mesh structure formed at 180°C has weak connectivity, and many linear structures are cut out from the sheet structure, which may be due to the enhanced etching effect caused by high temperature.
[0046] In order to verify the role of metal precursors such as iron and zinc, only palladium precursor was added to comparative example 1, and palladium precursor and tin precursor were added to comparative example 2. In comparative example 1, complete Pd nanoflowers were synthesized without adding tin and iron precursors, showing the neat morphology of self-assembled flower-like nanosheets ( Figure 6 ). This nanomaterial is complete in shape and has no visible holes from the magnified TEM image. Comparative Example 2 synthesized PdSn nanosheets, which are different in structure from Pd nanosheets in that the nanosheet assemblies are obviously curled and irregular ( Figure 7 ), which may be due to the tensile strain effect caused by the insertion of tin atoms with larger radius into the palladium face-centered cubic structure, the nanosheet is still intact as a whole, and no network structure appears. The structure of PdSn nanosheets synthesized without iron and zinc precursors proves the key role of acetic acid etching of iron and zinc in the formation of a highly porous network structure.
[0047] X-ray diffraction (XRD) was used to further study the crystal structure of the prepared carbon-supported catalyst ( Figure 8 ). The XRD patterns of Pd nanosheets / C, PdSn nanosheets / C and PdSn nanomesh / C all show a typical face-centered cubic structure, indicating that the structures of PdSn nanosheets / C and PdSn nanomesh / C are substitutional solid solution alloy phases. Compared with Pd nanosheets / C, the diffraction peaks of PdSn nanosheets / C and PdSn nanomesh / C shift negatively, which is because Pd is replaced by Sn atoms with larger atomic radius.
[0048] The electrochemical active area of commercial Pd / C catalyst (purchased from Johnson Matthey Catalyst Company) and synthesized carbon-supported catalyst was tested by CO stripping experiment. The results (Table 1) show that the electrochemical active area of Pd nanosheets / C (39.4 m 2 / g Pd )、PdSn nanosheets / C(41.7 m 2 / g Pd ), the electrochemical active area of PdSn nanomesh / C is significantly increased to 57.0 m 2 / g Pd , and even better than commercial Pd / C catalysts. This can be attributed to the fact that the network structure increases the number of exposed sites of the catalyst, and the larger electrochemical active area helps to make full use of the precious metals, which is conducive to the improvement of mass activity.
[0049] Table 1 Electrochemical active area of catalysts catalyst <![CDATA[Electrochemical active area (m 2 / g Pd )]]> Commercial Pd / C 50.8 Pd nanosheets (Comparative Example 1) / C 39.4 PdSn nanosheets (Comparative Example 2) / C 41.7 PdSn nanomesh (Example 1) / C 57.0 The specific surface area activities and mass activities of commercial Pd / C catalysts and carbon-supported catalysts for electrocatalytic ethanol oxidation were evaluated in 1 M NaOH + 1 M ethanol electrolyte at a scan rate of 50 mV / s. Fig. 9 a shows the specific surface area activity of the four carbon-supported catalysts. The specific surface area activity of PdSn nanomesh / C is calculated to be 22.1 mA / cm 2 , which is lower than commercial Pd / C (3.1mA / cm 2 ), Pd nanosheets / C (5.2 mA / cm 2 ) and PdSn nanosheets / C (8.8 mA / cm 2 ) are about 7.1 times, 4.3 times and 2.5 times higher in specific surface area, respectively. The mass activity of PdSn nanonet / C is still very outstanding, such as Fig. 9 As shown in b, PdSn nanonet / C (10.8 A / mg Pd ) is also much higher than commercial Pd / C (1.1 A / mg Pd )、Pd nanosheets / C(2.1 A / mg Pd ) and PdSn nanosheets / C (3.9 A / mgPd ).
[0050] By analyzing the components of the solution at different potentials, the products of electrocatalytic ethanol oxidation on different carbon-supported catalysts can be quantified ( Fig.10 ). It is noteworthy that the Faradaic efficiency of C1 product on PdSn nanomesh / C is 31.0%, 27.1% and 21.3% at 0.6 V, 0.7 V and 0.8 V, which is much higher than that of the other three catalysts. The significantly improved Faradaic efficiency of C1 product emphasizes the special role of PdSn nanomesh / C in promoting the breakage of CC bond during the oxidation of ethanol molecules, which greatly contributes to the improvement of ethanol oxidation activity.
[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing an ultrathin palladium-tin nanonet catalyst, characterized in that: The following steps are involved: (1) Mix N,N-dimethylformamide and etchant evenly; (2) dissolving the precursor, sacrificial pore-forming material, and tungsten hexacarbonyl in the mixed solution of step (1), heating the solution at high temperature, cooling the solution to room temperature, and washing the solution by centrifugation to obtain an ultrathin palladium-tin nanonet catalyst; The precursors are palladium metal salt and tin metal salt; the sacrificial pore-forming substance is at least one of iron metal salt and zinc metal salt.
2. The preparation method according to claim 1, characterized in that: The palladium metal salt is sodium chloropalladate, and the tin metal salt is tin chloride.
3. The preparation method according to claim 1, characterized in that: The iron metal salt is ferric chloride, and the zinc metal salt is zinc chloride.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the sodium chloropalladate to tin chloride is 1-1.5:
1.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the precursor to the sacrificial pore-forming material is 2-3:
1.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the precursor to tungsten hexacarbonyl is 1:1.5-2.
7. The preparation method according to claim 1, characterized in that: The etchant is acetic acid; the volume ratio of the N,N-dimethylformamide to the etchant is 4-5:
1.
8. The preparation method according to claim 1, characterized in that: The target temperature of the high temperature heating is 140°C-180°C, and the target temperature is heated within 15 minutes, and the heating time is 1-1.5 hours.
9. An ultra-thin palladium-tin nanonet catalyst, characterized in that: The ultra-thin palladium-tin nano-mesh catalyst is prepared by the preparation method according to any one of claims 1 to 8, and its electrochemical active area is 55-60 m 2 / g Pd , with an ultra-thin structure with a thickness of less than 1 nm.
10. Use of the ultrathin palladium tin nanomesh catalyst according to claim 9 in direct ethanol fuel cells or electrocatalytic ethanol oxidation.
Citation Information
Patent Citations
Palladium-tin-nickel ternary metallic nano electrocatalyst for fuel cell ethanol oxidation reaction and preparation method and application thereof
CN103825034A
Palladium-tin nano-chain network catalyst and preparation method and application thereof
CN108346808A
Carbon-supported palladium-tin tantalum nitride nano electrocatalyst for direct ethanol and methanol fuel cells and preparation method of carbon-supported palladium-tin tantalum nitride nano electrocatalyst
CN113745552A
Preparation and application of binary palladium-tin nano-alloy catalyst loaded on selenium-doped MXene
CN115312790A
Preparation method and application of phosphorus-doped palladium-molybdenum alloy ultrathin two-dimensional nano material
CN117862518A